A High‐Performing Solution‐Processed Small Molecule:Perylene Diimide Bulk Heterojunction Solar Cell. (21st June 2013) - Sharenko, Alexander; Proctor, Christopher M.; van der Poll, Thomas S.; Henson, Zachary B.; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.
<x xml:space="preserve">Abstract</x> By combining the molecular donor p‐DTS(FBTTh2)2 with a readily produced perylene diimide acceptor we are able to achieve a power conversion efficiency of 3.0%, making this one of the most efficient non‐fullerene organic solar cells to date. The reduced power conversion efficiency of the present system compared to the use of phenyl‐C71‐butyric acid methyl ester as an electron acceptor is shown to primarily be related to a significant reduction in the internal quantum efficiency. These results indicate the potential of small‐molecule:non‐fullerene bulk‐heterojunction organic photovoltaics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>